Sex and base excision repair as key susceptibility factors for alkylation-induced mutations, toxicity and hepatic cancer - Jennifer E. Kay; Joshua J. Corrigan; Lindsay B. Volk; Amanda L. Armijo; Norah A. Owiti; Lee J. Pribyl; Ilana S. Nazari; Dorothea K. Torous; Svetlana L. Avlasevich; Robert G. Croy; Dushan N. Wadduwage; Sebastian E. Carrasco; et al. (DNA Repair, 2026)

Relative effectiveness of high-dose versus standard-dose influenza vaccine against hospitalizations and mortality according to Charlson Comorbidity Index: A post-hoc analysis of the DANFLU-1 randomized trial - Katrine Feldballe Bernholm; Niklas Dyrby Johansen; Caroline Espersen; Daniel Modin; Kira Janstrup Hyldekær; Joshua Nealon; Sandrine Samson; Matthew M. Loiacono; Rebecca C. Harris; Carsten Schade Larsen; Anne Marie Reimer Jensen; Nino Emanuel Landler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose The DANFLU-1 trial suggested lower incidence of hospitalizations for pneumonia and influenza, respiratory disease and all-cause mortality among older adults receiving high-dose (HD-IV) versus standard-dose (SD-IV) influenza vaccine. This study assessed the relative effectiveness of HD-IV versus SD-IV according to comorbidity in elderly individuals. Methods This was a post-hoc analysis of the DANFLU-1 randomized controlled feasibility trial of HD-IV versus SD-IV conducted during the 2021–2022 influenza season in adults aged 65–79 years. Outcomes assessed included influenza-related, respiratory, and cardiovascular hospitalizations, and mortality. We tested for effect modification by level of the Charlson Comorbidity Index (CCI) using ICD-10 codes up to 10 years prior to randomization. Results Of the 12,477 randomly assigned participants (mean age 71.7 ± 3.9 years, 47.1% female), 8,020 (64.3%) had CCI = 0, 3,560 (28.5%) had CCI = 1–2 and 893 (7.2%) had CCI ≥ 3. When comparing HD-IV with SD-IV, hazard ratios of hospitalizations for pneumonia and influenza were similar across CCI groups (HR [95%CI]: 0.15 [0.03–0.68] for CCI = 0, 0.36 [0.11–1.15] for CCI = 1–2, 1.00 [0.25-4.00] for CCI ≥ 3). Comparable patterns were found for hospitalizations for respiratory disease (0.46 [0.17–1.20] for CCI = 0, 0.67 [0.32–1.39] for CCI = 1–2, 0.66 [0.24–1.87] for CCI ≥ 3) and all-cause mortality (0.28 [0.09–0.86] for CCI = 0, 0.70 [0.30–1.63] for CCI = 1–2, 0.57 [0.24–1.36] for CCI ≥ 3). There was no statistical evidence of effect modification by CCI for any outcome. Conclusions The lower incidences of clinical outcomes for HD-IV compared to SD-IV were not significantly modified by CCI. The potential benefit of HD-IV versus SD-IV may therefore be applicable regardless of comorbidity burden. Further research is required to confirm these findings.

Heavy metal contamination in watermelon and orange across urban markets: a year-long assessment - Babafemi J. Laoye; Samson O. Mabayoje; Tolulope A. Ogunnusi; Oghenerobor B. Akpor (Vegetos, 2026)

P05-02 Impact of sub-chronic dioxin exposure on the cardiorenal syndrome - R. Courcoux; R. Souktani; G. Berge; M. Quétin; M. Le Garff; S. Placier; C. Samson; J. Hadchouel; M. Gervais (Toxicology Letters, 2025)

Sustainable biomass-clay-ZnWO4 combos for the abatement of benzenediols: Process optimization and dynamics for water purification - Moses O. Alfred; Samson B. Ibeh; Morenike O. Adesina; Damilare Olorunnisola; Eric T. Anthony; Chidinma G. Olorunnisola; Udochukwu J. Iwuchukwu; Olumide O. Oni; Oluwaferanmi B. Otitoju; Brigitte Helmreich; Nurudeen A. Oladoja; Martins O. Omorogie; et al. (Journal of Water Process Engineering, 2025)

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

CometChip enables parallel analysis of multiple DNA repair activities [DNA repair 106 (2021) 103176–103202] - Jing Ge; Le P. Ngo; Simran Kaushal; Ian J. Tay; Elina Thadhani; Jennifer E. Kay; Patrizia Mazzucato; Danielle Chow; Jessica Fessler; David M. Weingeist; Robert W. Sobol; Leona D. Samson; et al. (DNA Repair, 2024)

Novel PHOTOPERIOD-1 gene variants associate with yield-related and root-angle traits in European bread wheat - Manar Makhoul; Rica-Hanna Schlichtermann; Samson Ugwuanyi; Sven E. Weber; Kai P. Voss-Fels; Andreas Stahl; Holger Zetzsche; Benjamin Wittkop; Rod J. Snowdon; Christian Obermeier (Theoretical and Applied Genetics, 2024)
Key message PHOTOPERIOD-1 homoeologous gene copies play a pivotal role in regulation of flowering time in wheat. Here, we show that their influence also extends to spike and shoot architecture and even impacts root development. Abstract The sequence diversity of three homoeologous copies of the PHOTOPERIOD-1 gene in European winter wheat was analyzed by Oxford Nanopore amplicon-based multiplex sequencing and molecular markers in a panel of 194 cultivars representing breeding progress over the past 5 decades. A strong, consistent association with an average 8% increase in grain yield was observed for the PpdA1-Hap1 haplotype across multiple environments. This haplotype was found to be linked in 51% of cultivars to the 2NS/2AS translocation, originally introduced from Aegilops ventricosa , which leads to an overestimation of its effect. However, even in cultivars without the 2NS/2AS translocation, PpdA1-Hap1 was significantly associated with increased grain yield, kernel per spike and kernel per m 2 under optimal growth conditions, conferring a 4% yield advantage compared to haplotype PpdA1-Hap4. In contrast to Ppd-B1 and Ppd-D1 , the Ppd-A1 gene exhibits novel structural variations and a high number of SNPs, highlighting the evolutionary changes that have occurred in this region over the course of wheat breeding history. Additionally, cultivars carrying the photoperiod-insensitive Ppd-D1a allele not only exhibit earlier heading, but also deeper roots compared to those with photoperiod-sensitive alleles under German conditions. PCR and KASP assays have been developed that can be effectively employed in marker-assisted breeding programs to introduce these favorable haplotypes.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Influence of pH and salts on DMF-DMA derivatization for future Space Applications - D. Boulesteix; A. Buch; J. Samson; M. Millan; J. Jomaa; D. Coscia; V. Moulay; O. McIntosh; C. Freissinet; J.C. Stern; C. Szopa (Analytica Chimica Acta, 2023)

Factors associated with foot-and-mouth disease seroprevalence in small ruminants and identification of hot-spot areas in northern Nigeria - Mattia Begovoeva; David O. Ehizibolo; Adeyinka J. Adedeji; Moses O. Oguche; Olumuyiwa Oyekan; Sandra I. Ijoma; Rebecca B. Atai; Yiltawe Wungak; Banenat B. Dogonyaro; David D. Lazarus; Mark Samson; Hussaini Ularamu; et al. (Preventive Veterinary Medicine, 2023)

Gaseous exchange and photosynthetic efficiency of fertigated indeterminate tomatoes (Solanum lycopersicum) - Mlungisi F. Mngoma; Lembe S. Magwaza; Shirly T. Magwaza; Nkanyiso J. Sithole; Asanda Mditshwa; Samson Z. Tesfay (Plant Physiology Reports, 2022)

Hematology and biochemical values in equines naturally infected with Theileria equi in Nigeria - ThankGod E. Onyiche; Ephraim Igwenagu; Samson A. Malgwi; Isaac J. Omeh; Abdullahi A. Biu; Oriel Thekisoe (Tropical Animal Health and Production, 2022)

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Oxide mineralogy and trace element chemistry as an index to magma evolution and Marathon-type mineralization in the Eastern Gabbro of the alkaline Coldwell Complex, Canada - M. J. Brzozowski; I. M. Samson; J. E. Gagnon; D. J. Good; R. L. Linnen (Mineralium Deposita, 2021)

Effects of fluid-induced oxidation on the composition of Fe–Ti oxides in the Eastern Gabbro, Coldwell Complex, Canada: implications for the application of Fe–Ti oxides to petrogenesis and mineral exploration - Matthew J. Brzozowski; Iain M. Samson; Joel E. Gagnon; Robert L. Linnen; David J. Good (Mineralium Deposita, 2021)

Five hundred million years of punctuated addition of juvenile crust during extension in the Goochland Terrane, central Appalachian Piedmont Province - Aaron J. Martin; Irene Kadel-Harder; Brent E. Owens; Kouki Kitajima; Scott D. Samson; Sanjeet K. Verma (International Geology Review, 2020)

Correction to: Chimpanzee (Pan troglodytes schweinfurthii) Group Sleep and Pathogen-Vector Avoidance: Experimental Support for the Encounter-Dilution Effect - David R. Samson; Luke A. Louden; Katie Gerstner; Samantha Wylie; Ben Lake; Bradley J. White; Charles L. Nunn; Kevin D. Hunt (International Journal of Primatology, 2019)

Chimpanzee (Pan troglodytes schweinfurthii) Group Sleep and Pathogen-Vector Avoidance: Experimental Support for the Encounter-Dilution Effect - David R. Samson; Luke A. Louden; Katie Gerstner; Samantha Wylie; Ben Lake; Bradley J. White; Charles L. Nunn; Kevin D. Hunt (International Journal of Primatology, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Diffusion pathways of Fe2+ and Fe3+ during the formation of ferrian chromite: a µXANES study - F. Gervilla; M. P. Asta; l. Fanlo; D. Grolimund; D. Ferreira-Sánchez; V. A. Samson; D. Hunziker; V. Colas; J. M. González-Jiménez; T. N. Kerestedjian; I. Sergeeva (Contributions to Mineralogy and Petrology, 2019)

Penicillium hermansii, a new species causing smoky mould in white button mushroom production - J. Houbraken; K. A. Seifert; R. A. Samson (Mycological Progress, 2019)

The assessment of the genotoxicity of e-waste leachates from e-waste dumpsites in Metro Manila, Philippines - Z. F. Alam; A. J. V. Riego; J. H. R. P. Samson; S. A. V. Valdez (International Journal of Environmental Science and Technology, 2019)

Making the Otolith Magnesium Chemical Calendar-Clock Tick: Plausible Mechanism and Empirical Evidence - Karin E. Limburg; Mark J. Wuenschel; Karin Hüssy; Yvette Heimbrand; Melvin Samson (Reviews in Fisheries Science & Aquaculture, 2018)

Prevalence and risk factors associated with bovine brucellosis in herds under extensive production system in southwestern Nigeria - Akwoba Joseph Ogugua; Victor Oluwatoyin Akinseye; Eniola O. Cadmus; Emmanuel A. Jolaoluwa Awosanya; Peter Ibukun Alabi; Olugbenga S. Idowu; Samson A. Akinade; Emma J. Dale; Lorraine Perrett; Andrew Taylor; Moriyon Ignocio; Simeon I. B. Cadmus (Tropical Animal Health and Production, 2018)

The Impact of Experimental Temperature and Water Level Manipulation on Carbon Dioxide Release in a Poor Fen in Northern Poland - Mateusz Samson; Sandra Słowińska; Michał Słowiński; Mariusz Lamentowicz; Jan Barabach; Kamila Harenda; Małgorzata Zielińska; Bjorn J. M. Robroek; Vincent E. J. Jassey; Alexandre Buttler; Bogdan H. Chojnicki (Wetlands, 2018)

Quantifying the influence of geography and environment on the northeast Atlantic mackerel spawning distribution - Thomas Brunel; Cindy J. G. van Damme; Melvin Samson; Mark Dickey‐Collas (Fisheries Oceanography, 2018)
Mackerel ( Scomber scombrus ) in the northeast Atlantic have shown changes in distribution at certain times of the year, which have impacted their exploitation and management. In this study, mackerel spawning habitat over 21 recent years was characterised using generalised additive modelling, based on spatial egg density data collected every third year during targeted ichthyoplankton surveys. Mackerel spawning distribution was found to depend primarily on geographical variables (coordinates and bottom depth), with preferred spawning locations on the shelf‐edge from the north of the Iberian peninsula to the west of Scotland, with a maximum west of Ireland. Environmental drivers had a lesser influence on egg distribution. Dome shaped relationships were found with temperature and mixed layer depth, with respective optimum at 13°C and around –300 m. The model was used to reconstruct maps of the potential habitat (areas where conditions were suitable, but not necessarily used, for spawning). Little changes were observed over the years in the potential habitat, suggesting that the expansion of the egg distribution (realised habitat) was not triggered by changes in the environmental variables investigated. Little evidence was found for density‐dependent habitat selection. There was a tendency for mackerel to make more use of areas of lesser suitability in years with large stock size (1992 and 2010). This pattern, however, broke down in 2013, when stock size was the highest, as spawning occurred very south and concentrated in the most suitable habitat.

Prioritisation of native legume species for further evaluation as potential forage crops in water-limited agricultural systems in South Africa - Francuois L. Müller; Lincoln M. Raitt; Samson B. M. Chimphango; M. Igshaan Samuels; Clement F. Cupido; J. Stephen Boatwright; Richard Knight; Marike Trytsman (Environmental Monitoring and Assessment, 2017)

Complex motor task associated with non-linear BOLD responses in cerebro-cortical areas and cerebellum - Adnan A. S. Alahmadi; Rebecca S. Samson; David Gasston; Matteo Pardini; Karl J. Friston; Egidio D’Angelo; Ahmed T. Toosy; Claudia A. M. Wheeler-Kingshott (Brain Structure and Function, 2016)

Aureobasidium melanogenum: a native of dark biofinishes on oil treated wood - Elke J. van Nieuwenhuijzen; Jos A. M. P. Houbraken; Martin Meijer; Olaf C. G. Adan; Robert A. Samson (Antonie van Leeuwenhoek, 2016)

Biodegradation of pesticides using fungi species found in the aquatic environment - B. R. Oliveira; A. Penetra; V. V. Cardoso; M. J. Benoliel; M. T. Barreto Crespo; R. A. Samson; V. J. Pereira (Environmental Science and Pollution Research, 2015)

PTRF is associated with caveolin 1 at the time of receptivity: but SDPR is absent at the same time - Romanthi J. Madawala; Connie E. Poon; Samson N. Dowland; Christopher R. Murphy (Histochemistry and Cell Biology, 2015)

Consequence of altered nitrogen cycles in the coupled human and ecological system under changing climate: The need for long-term and site-based research - Hideaki Shibata; Cristina Branquinho; William H. McDowell; Myron J. Mitchell; Don T. Monteith; Jianwu Tang; Lauri Arvola; Cristina Cruz; Daniela F. Cusack; Lubos Halada; Jiří Kopáček; Cristina Máguas; et al. (Ambio, 2015)

Reflex testing for Lynch syndrome: If we build it, will they come? Lessons learned from the uptake of clinical genetics services by individuals with newly diagnosed colorectal cancer (CRC) - E. Tomiak; A. Samson; N. Spector; M. Mackey; C. Gilpin; E. Smith; D. Jonker; J. Allanson; T. Asmis (Familial Cancer, 2014)

Physico-chemical properties of tamarind (Tamarindus indica L.) fruits from Mali: selection of elite trees for domestication - N. Van den Bilcke; K. Alaerts; S. Ghaffaripour; D. J. Simbo; R. Samson (Genetic Resources and Crop Evolution, 2014)

Penicillium subrubescens, a new species efficiently producing inulinase - S. Mansouri; J. Houbraken; R. A. Samson; J. C. Frisvad; M. Christensen; D. E. Tuthill; S. Koutaniemi; A. Hatakka; P. Lankinen (Antonie van Leeuwenhoek, 2013)

Opportunities for domesticating the African baobab (Adansonia digitata L.): multi-trait fruit selection - David J. Simbo; Sebastiaan De Smedt; Nina Van den Bilcke; Bruno De Meulenaer; John Van Camp; Veronique Uytterhoeven; Filip Tack; Roeland Samson (Agroforestry Systems, 2013)

Exercise and diet-induced weight loss attenuates oxidative stress related-coronary vasoconstriction in obese adolescents - Zhaohui Gao; Marsha Novick; Matthew D. Muller; Ronald J. Williams; Samson Spilk; Urs A. Leuenberger; Lawrence I. Sinoway (European Journal of Applied Physiology, 2013)

The roles of magmatic and hydrothermal processes in PGE mineralization, Ferguson Lake deposit, Nunavut, Canada - Nelson O. Campos-Alvarez; Iain M. Samson; Brian J. Fryer (Mineralium Deposita, 2012)

Immunotoxicity of Tannery Effluent to the Freshwater Fish Cyprinous carpio - A. G. Murugesan; A. Ramathilaga; J. K. Samson Ponselvan; R. Dinagaran Michael (Bulletin of Environmental Contamination and Toxicology, 2012)

Age-related differences in force variability and visual display - Edward Ofori; Jean M. Samson; Jacob J. Sosnoff (Experimental Brain Research, 2010)

Computational models of reinforcement learning: the role of dopamine as a reward signal - R. D. Samson; M. J. Frank; Jean-Marc Fellous (Cognitive Neurodynamics, 2010)

Impact of durum wheat milling on deoxynivalenol distribution in the outcoming fractions - G. Ríos; N. Zakhia-Rozis; M. Chaurand; F. Richard-Forget; M.F. Samson; J. Abecassis; V. Lullien-Pellerin (Food Additives & Contaminants: Part A, 2009)

Effect of legume plant density and mixed culture on symbiotic N2 fixation in five cowpea (Vigna unguiculata L. Walp.) genotypes in South Africa - Joachim H. J. R. Makoi; Samson B. M. Chimphango; Felix D. Dakora (Symbiosis, 2009)

Variation in abundance across a species' range predicts climate change responses in the range interior will exceed those at the edge: a case study with North American beaver - STACEY I. JAREMA; JASON SAMSON; BRIAN J. MCGILL; MURRAY M. HUMPHRIES (Global Change Biology, 2009)
The absence of information about how abundance varies across species' ranges restricts most modeling and monitoring of climate change responses to the range edge. We examine spatial variation in abundance across the northeastern range of North American beaver ( Castor canadensis ), evaluate the extent to which climate and nonclimate variables explain this variation, and use a species–climate envelope model that includes spatial variation in abundance to predict beaver abundance responses to projected climate change. The density of beaver colonies across Québec follows a roughly logistic pattern, with high but variable density across the southern portion of the province, a sharp decline in density at about 49°N, and a long tail of low density extending as far as 58°N. Several climate and nonclimate variables were strong predictors of variation in beaver density, but 97% of the variation explained by nonclimate variables could be accounted for by climate variables. Because of the peak and tail density pattern, beaver climate sensitivity (change in density per unit change in climate) was greatest in the interior and lowest at the edge of the range. Combining our best density–climate models with projections from general circulation models (GCM) predicts a relatively modest expansion of the species' northern range limit by 2055, but density increases in the range interior that far exceed those at the range edge. Thus, some of the most dramatic responses to climate change may be occurring in the core of species' ranges, far away from the edge‐of‐the‐range focus of most current modeling and monitoring efforts.

Variation in abundance across a species' range predicts climate change responses in the range interior will exceed those at the edge: a case study with North American beaver - STACEY I. JAREMA; JASON SAMSON; BRIAN J. MCGILL; MURRAY M. HUMPHRIES (Global Change Biology, 2008)

Effects of the toxic dinoflagellate, Alexandrium fundyense on three species of larval fish: a food‐chain approach - J. C. Samson; S. E. Shumway; J. S. Weis (Journal of Fish Biology, 2008)
Sublethal behavioural effects of exposure to paralytic shellfish toxins (PST; saxitoxin and its derivatives) from the toxic dinoflagellate Alexandrium fundyense were investigated in newly settled winter flounder Pseudopleuronectes americanus , larval sheepshead minnow Cyprinodon variegatus and larval mummichog Fundulus heteroclitus through an A. fundyense –copepod–fish food chain. Consumption of as few as six to 12 toxin‐containing copepods was lethal to the fishes. After consuming fewer toxin‐containing copepods, all three fish species exhibited sublethal effects from vector‐mediated exposure. Prey‐capture ability of mummichogs was reduced in larvae that had consumed toxic copepods, Coullana canadensis . After consuming toxic C. canadensis or mixed copepods, mummichog larvae had reduced swimming performance. Swimming activity was also significantly reduced in winter flounder after consuming toxic copepods, including time spent in motion and distance travelled. Prey capture and predator avoidance were reduced in first‐feeding sheepshead minnow larvae that had consumed toxic dinoflagellate cells. Adverse effects on prey capture or predator avoidance may reduce larval survival and facilitate the transmission of PST through the food web. This study provides baseline information on sublethal effects of PST exposure on fishes using a novel food‐chain approach with zooplankton as vectors.

Decreased expression of Intestinal I- and L-FABP levels in rare human genetic lipid malabsorption syndromes - S. Guilmeau; I. Niot; J. P. Laigneau; H. Devaud; V. Petit; N. Brousse; R. Bouvier; L. Ferkdadji; C. Besmond; L. P. Aggerbeck; A. Bado; M. E. Samson-Bouma (Histochemistry and Cell Biology, 2007)

Soil sampling for Metarhizium anisopliae spores in Queensland sugarcane fields - Mohamed N. Sallam; Catherine A. McAvoy; Peter R. Samson; Judy J. Bull (BioControl, 2007)

Evaluation of lethal and non‐lethal sampling methods for the detection of white sturgeon iridovirus infection in white sturgeon, Acipenser transmontanus (Richardson) - J D Drennan; S E LaPatra; C A Samson; S Ireland; K F Eversman; K D Cain (Journal of Fish Diseases, 2007)
Pectoral fin tissue of white sturgeon was investigated as a potential non‐lethal sample source for the detection of white sturgeon iridovirus (WSIV) infection. Histopathology and polymerase chain reaction (PCR) results using fin tissue were compared with the standard lethal histopathology sampling method that utilizes head tissue. Tissues for each of the three sampling methods were collected weekly for 8 weeks from individual sturgeon undergoing an experimental cohabitation challenge with fish infected with the Abernathy isolate of WSIV. Non‐lethal fin histopathological evaluation did not reveal infection during the first 3 weeks of sampling, while non‐lethal PCR and the lethal method were variable. However, all three sampling methods were equally capable of identifying infection from 4 to 8 weeks post‐exposure. Of the survivors tested, all were negative by PCR and the lethal method, and only one fish was identified as being positive by non‐lethal fin histopathology. In another experiment, all three sampling methods were applied to asymptomatic WSIV carriers in a case study conducted at the Kootenai Tribal Sturgeon Conservation Hatchery. Results showed that both lethal and non‐lethal fin histopathology were equally effective in detecting infection, but PCR was unable to identify this strain of WSIV. Depending on the virus isolate, these results suggest that non‐lethal sampling of fin tissue (histopathology or PCR) is comparable with the lethal sampling method at identifying WSIV infection once infection is established, and under certain circumstances may provide an alternative to lethal sampling.

Effect of danofloxacin (Advocin A180) on goats affected with contagious caprine pleuropneumonia - U. Ozdemir; G. R. Loria; K. S. Godinho; R. Samson; T. G. Rowan; C. Churchward; R. D. Ayling; R. A. J. Nicholas (Tropical Animal Health and Production, 2006)

Potential Use of the Plant Antioxidant Network For Environmental Exposure Assessment of Heavy Metals in Soils - E. Meers; A. Ruttens; W. Geebelen; J. Vangronsveld; R. Samson; K. Vanbroekhoven; M. Vandegehuchte; L. Diels; F. M. G. Tack (Environmental Monitoring and Assessment, 2006)

O6-Methylguanine-DNA Methyltransferase Leu84Phe and Ile143Val Polymorphisms and Risk of Colorectal Cancer in the Nurses’ Health Study and Physicians’ Health Study (United States) - Gregory J. Tranah; James Bugni; Edward Giovannucci; Jing Ma; Charles Fuchs; Lisa Hines; Leona Samson; David J. Hunter (Cancer Causes & Control, 2006)

Forest resource assessment in mohand forest range, Uttar Pradesh using remote sensing and GIS - I. J. singh; D. K. Jugran; Samson Thanruma; S. R. Reddy (Journal of the Indian Society of Remote Sensing, 2005)

Site-specific Approaches to Cotton Insect Control. Sampling and Remote Sensing Analysis Techniques - J. L. Willers; J. N. Jenkins; W. L. Ladner; P. D. Gerard; D. L. Boykin; K. B. Hood; P. L. McKibben; S. A. Samson; M. M. Bethel (Precision Agriculture, 2005)

Species Extinction in the Marine Environment: Tasmania as a Regional Example of Overlooked Losses in Biodiversity - GRAHAM J. EDGAR; CATH R. SAMSON; NEVILLE S. BARRETT (Conservation Biology, 2005)
We used Tasmania as a case example to question the consensus that few marine species have recently become extinct or are approaching extinction. Threats to marine and estuarine species—primarily in the form of climate change, invasive species, fishing, and catchment discharges—are accelerating, fully encompass species ranges, and are of sufficient magnitude to cause extinction. Our ignorance of declining biodiversity in the marine environment largely results from an almost complete lack of systematic broad‐scale sampling and an overreliance on physicochemical data to monitor environmental trends. Population declines for marine species approaching extinction will generally go unnoticed because of the hidden nature of their environment and lack of quantitative data.

Aspergillus vadensis, a new species of the group of black Aspergilli - Ronald P. de Vries; Jens C. Frisvad; Peter J. I. van de Vondervoort; Kim Burgers; Angelina F. A. Kuijpers; Robert A. Samson; Jaap Visser (Antonie van Leeuwenhoek, 2005)

Exploring the Penicillium marneffei genome - Kwok-yung Yuen; Géraldine Pascal; Samson S. Y. Wong; Philippe Glaser; Patrick C. Y. Woo; Frank Kunst; James J. Cai; Elim Y. L. Cheung; Claudine Médigue; Antoine Danchin (Archives of Microbiology, 2003)

Real-time RT-PCR quantitation of mCLCA1 and mCLCA2 reveals differentially regulated expression in pre- and postnatal murine tissues - Ina Leverkoehne; Bettina A. Horstmeier; Georg von Samson-Himmelstjerna; Bob J. Scholte; Achim D. Gruber (Histochemistry and Cell Biology, 2002)

Nucleotide sequence of the 5′-terminus of Newcastle disease virus and assembly of the complete genomic sequence: agreement with the “rule of six” - R. J. Phillips; A. C. R. Samson; P. T. Emmerson (Archives of Virology, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Penicillium discolor, a new species from cheese, nuts and vegetables - Jens C. Frisvad; Robert a. Samson; Birgitte R. Rassing; Marjolein I. van der Horst; F.T.J. van Rijn; J. Stark (Antonie van Leeuwenhoek, 1997)

Detection of potato leafroll virus by visual inspection, direct tissue blotting and ELISA techniques - J. L. Whitworth; R. G. Samson; T. C. Allen; A. R. Mosley (American Journal of Potato Research, 1993)

Sequence analysis of temperature sensitive and ?neuraminidase-tolerant? mutants of Newcastle disease virus (strain Beaudette C) - J. Hughes; K. Yusoff; R. Hardy; H. McCartney; P. T. Emmerson; A. C. R. Samson (Archives of Virology, 1991)

Chemotaxonomy of the genus Talaromyces - J. C. Frisvad; O. Filtenborg; R. A. Samson; A. C. Stolk (Antonie van Leeuwenhoek, 1990)

Preliminary studies on the efficacy and establishment ofRoptrocerus xylophagorum [Hym.: Torymidae], a parasitoid ofIps grandicollis [Col.: Scolytidae], in Australia - P. R. Samson; J. Smibert (BioControl, 1986)

On the taxonomy of the entomogenous fungus Filobasidiella arachnophila - R. A. Samson; J. A. Stalpers; A. C. M. Weijman (Antonie van Leeuwenhoek, 1983)

Additional notes on species ofAspergillus, Eurotium andEmericella from Egyptian desert soil - R. A. Samson; J. Mouchacca (Antonie van Leeuwenhoek, 1975)

Some interesting species of Emericella and Aspergillus from Egyptian desert soil - R. A. Samson; J. Mouchacca (Antonie van Leeuwenhoek, 1974)

The relation of cumulative amount and frequency of rainfall and mean temperature to late blight in Indiana - J. R. Wallin; R. W. Samson (American Journal of Potato Research, 1953)